Auditoría financiera a la constructora toapanta santa María Toasan S.A y la incidencia sobre su rentabilidad período 2012 - Fiallos Niza, Viviana Elizabe (2014)
The contents of this research paper summarizes the results of the execution of the Construction Financial Audit TOASAN SA on improving the accounting and financial processes and understand the impact on profitability period 2012. The project theme was chosen based on the need that the company had an assessment at its current internal control, and each of the Accounting Process that develops through a Financial Audit will be accomplished to know your actual financial situation , and based on results take measures to optimize the profitability of the company. With the implementation of audit processes and the use of International Standards on Auditing and International Financial Reporting Standards for SMEs which specific findings to administrators Company provided recommendations to thereby take corrective Detected needed to improve their shortcomings. The research project contains the introduction, rationale, objectives , assumptions, theoretical framework and research results detailing the audit process with their supporting documents.